A Modern Pilgrim in Mecca and a Siege in Sanaa: By John Byng Wavell (Reading, UK: Garnet Publishing, 2005. 349 pages.) (American Journal of Islam and Society, 2007)
It should be noted that the trespassing English pilgrim Arthur Wavell is definitelynot postmodern; his “modern” account of a trip in disguise to Makkahand Madinah was originally published in 1912. The author revels in explaininghow he pulled off the role of a Zanzibar Muslim on hajj, as though heis presenting a how-to guide for fellow swashbucklers. Previously, he hadcarried out intelligence work for the British Army in South Africa and, in1906, settled on a farm near Mombasa, where he learned Arabic and metMuslims. He died at the young age of thirty-four while fighting in EastAfrica.Wavell presents a riveting tale with a self-serving hubris that could easilybe dismissed as a remake of Sir Richard Burton’s earlier and more celebratedpenetration of Makkah. But there is good reason to read this datedbook, if only for the historical view of travel to Makkah near the end of theOttoman caliphate. Wavell traveled from Damascus on the Hijaz railway thevery year (1908) that it reached Makkah. His trip was made partly out ofcuriosity, no doubt fueled by the fact non-Muslims are forbidden to enter ...